2008
DOI: 10.1080/09595230801956124
|View full text |Cite
|
Sign up to set email alerts
|

Comparing heroin users and prescription opioid users in a Canadian multi‐site population of illicit opioid users

Abstract: Our study underscores the increasing prevalence of PO compared to heroin use in the study population. Differences between PO-only and H-only users were more pronounced than differences between PO-only and PO & H users. PO-only use may be associated with lowered health risks and social burdens, yet concerns regarding polysubstance use and drug sourcing arise. Challenges for targeted interventions are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 46 publications
(36 reference statements)
6
50
3
Order By: Relevance
“…However, previous cross-sectional research of urban opioid users found no significant association between prescription opioid use and non-fatal overdose (36, 37). This is inconsistent with our results, which add a longitudinal perspective to the issue, and suggest that urban IDU who use prescription opioids are in fact at a higher risk of non-fatal overdose.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, previous cross-sectional research of urban opioid users found no significant association between prescription opioid use and non-fatal overdose (36, 37). This is inconsistent with our results, which add a longitudinal perspective to the issue, and suggest that urban IDU who use prescription opioids are in fact at a higher risk of non-fatal overdose.…”
Section: Discussionmentioning
confidence: 70%
“…Notably, another Canadian study found that people who used prescription opioids were more likely to report using benzodiazepines and cocaine (36), both of which are well-documented risk factors for overdose, especially when used concurrently with opioids (19, 37, 3944). While neither benzodiazepine use nor daily cocaine use was significantly associated with non-fatal overdose in our study, it is plausible that the people who use prescription opioids in our sample have a more complex polysubstance profile than those who do not.…”
Section: Discussionmentioning
confidence: 99%
“…Although rates vary geographically, recent estimates of prescription drug misuse among IDUs were 80–91% (Fischer et al 2008; Havens, Walker & Leukefeld 2007). The risks associated with injection of illicit drugs and transmission of blood-borne infections, such as hepatitis C (HCV) and HIV, due to shared needles, drug solutions, and drug equipment, frequent injection, and young age at injection initiation are well documented (Chaisson et al 1987; Doherty et al 2000; Garfein et al 1996; Green et al 1993; Jose et al 1993; Nelson et al 2002; Schoenbaum et al 1989; Shah et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…While several studies have looked at prescription drug misuse among illicit drug users (Davis & Johnson 2008; Firestone & Fischer 2008; Fischer et al 2008; Sigmon 2006), examining unsafe injection and sexual practices among those who inject prescription drugs has been understudied. A recent qualitative study conducted in Montreal found that the sharing of “washes,” or opioid residues, was a common practice among IDUs injecting prescription opioids (Roy, Arruda & Bourgois 2011), underscoring the need to identify risk behaviors among injectors of prescription medications.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially important because recent research has shown that those who abuse prescription opioids possess different characteristics than those who abuse illicit drugs, such as heroin. Specifically, studies have found that those who abuse prescription opioids had lower addiction severity, less intravenous (IV) drug 532 PARENTAL PRESCRIPTION OPIOID ABUSE 533 use, higher household stability, less sedative use, and less criminal involvement compared with those abusing heroin (14)(15)(16). Although these studies did not look exclusively at parental drug abuse, they suggest that those abusing prescription opioids possess a number of different characteristics compared with heroin users.…”
Section: Introductionmentioning
confidence: 90%